The impact of Covid-19 and the effect of psychological factors on training conditions of handball players - Mon-López, D.; de la Rubia Riaza, A.; Hontoria Galán, M.; Refoyo Roman, I. (International Journal of Environmental Research and Public Health, 2020)
The spread of COVID-19 has altered sport in Spain, forcing athletes to train at home. The objectives of the study were: (i) to compare training and recovery conditions before and during the isolation period in handball players according to gender and competitive level, and (ii) to analyse the impact of psychological factors during the isolation period. A total of 187 participants (66 women and 121 men) answered a Google Forms questionnaire about demographics, training, moods, emotional intelligence, and resilience sent using the snowball sampling technique. T-test and analysis of variance (ANOVA) were used to compare sport level and gender differences. Linear regressions were used to analyse the psychological influence on training. Handball players reduced training intensity (in the whole sample; p = 0.44), training volume (especially in professional female handball players; p < 0.001), and sleep quality (especially in professional male handball players; p = 0.21) and increased sleep hours (especially in non-professional female players; p = 0.006) during the isolation period. Furthermore, psychological factors affected all evaluated training and recovery conditions during the quarantine, except for sleep quantity. Mood, emotional intelligence, and resilience have an influence on physical activity levels and recovery conditions. In addition, training components were modified under isolation conditions at p < 0.001. We conclude that the COVID-19 isolation period caused reductions in training volume and intensity and decreased sleep quality. Furthermore, psychological components have a significant impact on training and recovery conditions.